Lowering low-density lipoprotein cholesterol levels in patients with type 2 diabetes mellitus - Bays, Harold E (Dove Medical Press, 2014)
Type 2 diabetes mellitus (T2DM) is characterized by hyperglycemia, insulin resistance, and/or progressive loss of β-cell function. T2DM patients are at increased risk of micro- and macrovascular disease, and are often considered as representing an atherosclerotic coronary heart disease (CHD) risk equivalent. Interventions directed at glucose and lipid level control in T2DM patients may reduce micro- and macrovascular disease. The optimal T2DM agent is one that lowers glucose levels with limited risk for hypoglycemia, and with no clinical trial evidence of worsening CHD risk. Lipid-altering drugs should preferably reduce low-density lipoprotein cholesterol and apolipoprotein B (apo B) and have evidence that the mechanism of action reduces CHD risk. Statins reduce low-density lipoprotein cholesterol and apo B and have evidence of improving CHD outcomes, and are thus first-line therapy for the treatment of hypercholesterolemia. In patients who do not achieve optimal lipid levels with statin therapy, or who are intolerant to statin therapy, add-on therapy or alternative therapies may be indicated. Additional available agents to treat hypercholesterolemic patients with T2DM include bile acid sequestrants, fibrates, niacin, and ezetimibe. This review discusses the use of these alternative agents to treat hypercholesterolemia in patients with T2DM, either as monotherapy or in combination with statin therapy.